2017
DOI: 10.1007/s11273-017-9583-6
|View full text |Cite
|
Sign up to set email alerts
|

High heterotrophic CO2 emissions from a Malaysian oil palm plantation during dry-season

Abstract: Tropical peatlands are currently being rapidly cleared and drained for the establishment of oil palm plantations, which threatens their globally significant carbon sequestration capacity. Large-scale land conversion of tropical peatlands is important in the context of greenhouse gas emission factors and sustainable land management. At present, quantification of carbon dioxide losses from tropical peatlands is limited by our understanding of the relative contribution of heterotrophic and autotrophic respiration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 23 publications
6
48
0
Order By: Relevance
“…The autotrophic contribution from a dense secondary peat forest was observed to be >50% of the total CO2 emissions (Murdiyarso et al, 2017), but the autotrophic component was almost non-existent at a cleared site and about half of the sampling points in other agricultural sites were away from vegetation. Therefore, it is highly likely that heterotrophic contribution from the forest is about 50% of the total emission while for 1 st generation oil palm it is >70% and for all the 2 nd generation plantations it is >80% of their respective total emissions, owing to the age of the oil palm in each plantations (Dariah et al, 2014;Comeau et al, 2016;Hergoualc'h et al, 2017;Matysek et al, 2017;Murdiyarso et al, 2017). Considering this, C loss through CO2 emissions were in the similar range (ca.…”
Section: Discussionmentioning
confidence: 95%
“…The autotrophic contribution from a dense secondary peat forest was observed to be >50% of the total CO2 emissions (Murdiyarso et al, 2017), but the autotrophic component was almost non-existent at a cleared site and about half of the sampling points in other agricultural sites were away from vegetation. Therefore, it is highly likely that heterotrophic contribution from the forest is about 50% of the total emission while for 1 st generation oil palm it is >70% and for all the 2 nd generation plantations it is >80% of their respective total emissions, owing to the age of the oil palm in each plantations (Dariah et al, 2014;Comeau et al, 2016;Hergoualc'h et al, 2017;Matysek et al, 2017;Murdiyarso et al, 2017). Considering this, C loss through CO2 emissions were in the similar range (ca.…”
Section: Discussionmentioning
confidence: 95%
“…In Riau province, the CO2 emission was reported higher at 66 ± 25 ton CO2 ha -1 year -1 (Husnain et al 2014). While in Malaysia, CO2 emission from oil palm plantation was ranging 22.1-117.5 ton CO2 ha -1 year -1 (Melling et al 2013;Ishikura et al 2018;Matysek et al 2018).…”
Section: Discussionmentioning
confidence: 97%
“…Several studies exhibited the effect of oil palm age on CO2 flux. Matysek et al (2018) found that the average soil respiration of year 2000 established oil palm plantation was 1.341 gCO2 m -2 hr -1 which is higher compared to soil respiration of oil plantation that was established in the year 1978 and replanted in the year 2006 (0.988 gCO2 m -2 hr -1 ) and they argued the decline of soil organic carbon at the second generation of plantation might be responsible for the difference.…”
Section: Discussionmentioning
confidence: 98%
“…Previous research on the effects of peat swamp forest disturbance has predominately focused on direct atmospheric GHG emissions from the peat surface (Couwenberg et al, 2010;Hooijer et al, 2010;Page et al, 2011;Hirano et al, 2012;Matysek et al, 2017). Until fairly recently, fluvial carbon losses received less attention, but more recent data suggest that this flux can represent a substantial fraction of the tropical peatland carbon balance (Moore et al, 2013;Evans et al, 2014;Rixen et al, 2016;Yupi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%